STUDI KOMPARATIF KEBARUAN DESAIN ARSITEKTUR TROPIS ANTARA KARYA AI DAN ARSITEK MANUSIA - Mulia, Endi Martha; Sitohang, Rasmi; Valery, Claudio (LPPM ISTP, 2025)
This study aims to evaluate and compare the novelty of tropical architectural designs generated by artificial intelligence (AI) and human architects. The rapid advancement of generative AI technologies has enabled the creation of unique and complex architectural forms; however, their relevance to tropical climatic contexts remains questionable. Using a mixed-method approach, this research integrates subjective assessments from a panel of tropical architecture experts with objective morphological analyses. The results indicate that AI-generated designs excel in visual novelty but often lack adaptation to critical tropical design principles, such as cross-ventilation, shading devices, and passive cooling strategies. Conversely, human architects produce designs with higher climatic responsiveness and sustainability, though they tend to be more conservative in terms of form innovation. These findings highlight the need for AI systems to incorporate localized climatic parameters to produce contextually relevant and sustainable architectural solutions.